The Relation of Immunoglobulin Class, Pattern of Antinuclear Antibody, and Complement-Fixing Antibodies to DNA in Sera from Patients with Systemic Lupus Erythematosus - Rothfield, Naomi F. (1967)
Sera from 55 patients with systemic lupus erythematosus were studied to clarify the significance of the patterns of nuclear fluorescence observed. The sera in which the IgG fraction produced a peripheral pattern of nuclear fluorescence were found to contain complement-fixing antibodies to native DNA and to DNA-histone complexes. This correlation did not exist when complement-fixing activity was compared to the IgM nuclear patterns. Sera which contained only complement-fixing antibodies to denatured DNA and which did not react with native DNA or nucleoprotein did not produce the peripheral pattern of nuclear fluorescence. The data suggest that single strands of DNA were not the reactive groups in the nucleus responsible for the peripheral pattern. The results support the conclusion that DNA within a DNA-protein complex may be the nuclear antigen responsible for the peripheral pattern of nuclear fluorescence. Analysis of the clinical data revealed that a close correlation existed between the presence of IgG peripheral pattern, complement-fixing antibodies to DNA and histone-DNA complexes, and clinical manifestation of active disease.